Transition Metal Photoredox Catalysis of Radical Thiol-Ene Reactions - Tyson, Elizabeth L. (2012)
[Image: see text] We describe the anti-Markovnikov hydrothiolation of olefins using visible light absorbing transition metal photocatalysts. The key thiyl radical intermediates are generated upon quenching of photoexcited Ru*(bpz)(3)(2) with a variety of thiols. The adducts of a wide variety of olefins and thiols are formed in excellent yield (73–99%).